Association between metabolic syndrome and hepatitis B virus infection in the Roma population in eastern Slovakia: a population-based study - Janičko, Martin; Senajová, Gabriela; Dražilová, Sylvia; Veselíny, Eduard; Fedačko, Ján; Siegfried, Leonard; Kristián, Pavol; Virág, Ladislav; Pella, Daniel; Mareková, Mária; Gecková, Andrea; Kalanin, Peter; et al. (Central European Journal of Public Health, 2014)
BACKGROUND: The simultaneous presence of chronic hepatitis B (CHB) and metabolic syndrome (MS) in the high-risk Roma community constitutes a high risk for liver cirrhosis and potentially hepatocellular carcinoma. This study aims to explore the relationship between MS and CHB. METHODS: Data from the cross-sectional HepaMeta Study conducted in Slovakia in 2011 among Roma living in rural communities were used. Participants were tested for the presence of MS, and lipid levels--total cholesterol, high density lipoproteins (HDL), low density lipoproteins (LDL), triglycerides (TG), apolipoprotein B100, and CHB HBsAg and anti-HBc IgG were also monitored. Viral load was measured in HBsAg-positive patients. RESULTS: A total of 452 patients were screened; MS was diagnosed in 29.6% of patients, and 12.5% had CHB. Anti-HBc IgG antibodies were present in 52.8% of patients. CHB patients had lower levels of total cholesterol (5.45 +/-1.21 vs. 4.71 +/- 1.23 mmol/l; p = 0.035), LDL cholesterol (median 2.2 mmol/l, interquartile range 0.88 mmol/l vs. 2.5 mmol/l, interquartile range 0.9 mmol/l; p = 0.01) and apolipoprotein B100 (median 0.66 mmol/l, interquartile range 0.26 mmol/l vs. 0.74 mmol/l, interquartile range 0.29 mmol/l; p = 0.025). Patients diagnosed with MS had a higher HBV DNA load than patients without MS (1,728.2 +/- 14.33 IU/ml vs. 12,779.1 +/- 20.9 IU/ml; p = 0.037). CHB patients with TC and apolipoprotein B100 within the reference range had a lower hepatitis B DNA (HBV DNA) load than patients with high or low values of TC or apolipoprotein B100. CONCLUSION: The prevalence of chronic hepatitis B and simultaneous presence of MS was high among Roma. HBsAg-positive patients had lower levels of total and LDL cholesterol along with decreased apolipoprotein B100. The viral load of chronic hepatitis B patients with MS was higher than in patients without MS.
Keywords: Comorbidity; biologické markery; Adolescent; venkovské obyvatelstvo; lidé středního věku; hepatitida B; komorbidita; Rural Population; lidé; Adult; Middle Aged; Apolipoprotein B-100; dospělí; metabolický syndrom; Female; průřezové studie; Slovenská republika; Cholesterol; Biomarkers; Lipids; Male; Roma; ženské pohlaví; Cross-Sectional Studies; Humans; lipidy; zdravotnické přehledy; apolipoprotein B-100; mužské pohlaví; Hepatitis B; Triglycerides; Metabolic Syndrome; triglyceridy; Romové; cholesterol; Health Surveys; Slovakia; mladiství